Risk Management Analysis of Zakat Management from the Perspective of Zakat Core Principle - Gunawan, Agung; Amin, Dikri Hamzah; Rojak, Fadel Mohamad; Hidayat, Ari; Sophanudin, Agus (Studi Multidisipliner: Jurnal Kajian Keislaman, 2025)
This study aims to analyze risk management in zakat management based on Zakat Core Principles (ZCP), which includes aspects of legal institutions, governance, supervision, risk management, intermediation functions, and compliance with sharia governance. The research method used is a descriptive method with a qualitative approach, equipped with in-depth interview techniques. The descriptive approach aims to provide a systematic, factual, and accurate picture of zakat management practices in the context of the management institution. The results of the study show that there are four main categories of risks in zakat management, namely reputational risk and muzakki loss, operational risk, distribution risk, and zakat transfer risk between countries. These risks have the potential to hinder the optimization of zakat management if they are not managed appropriately and systematically. Therefore, it is necessary to implement a risk management strategy that is integrated with the Zakat Core Principles to increase public trust and ensure a more effective, transparent, and sustainable distribution of zakat.